In a rapidly evolving education system, developing creativity competence in prospective teachers has become an important area of focus. Creativity is the ability to generate new ideas, propose innovative solutions, and approach problems from original pers - Dautova Bekposhsha Ergashevna (Scientific Trends, 2025)
This research study aims to analyze the impact of student-centered teaching methods on the development of creativity competence in future teachers. The main goal of the study was to identify the role of personalized learning strategies, teacher mentorship, and assessment systems in stimulating creative and innovative skills in students. During the experiment, participants were divided into four groups, each of which was taught using different methods: student-centered active learning methods, teacher involvement, and creative assessment. The Torrance Test of Creative Thinking was used to measure the level of students’ creativity. The ANOVA and Tukey HSD post-hoc tests were applied to analyze the data. The results of the experiment showed that student-centered active teaching methods and constant teacher mentorship significantly contribute to the development of creativity competence. The group that used active methods and systematic creative assessment demonstrated particularly high results, which confirmed the effectiveness of these approaches. At the same time, the group that did not use active methods and creative assessment showed significantly lower results. The comparative analysis revealed that the group where active methods were not applied, but teachers were actively involved in the process, also achieved higher outcomes compared to the group where only passive methods were used. This underlines the importance of teacher involvement and reflective assessment in the educational process.
Keywords: Creativity competence, student-centered learning, teacher education, active learning, pedagogical factors, teachers, creative assessment methods, project-based learning, inquiry-based learning, reflective practice, innovation, future teachers.